Effect of entomopathogenic nematodes on populations of the coffee berry borer, Hypothenemus hampei (Coleoptera: Scolytidae), in berries on the soil - LARA-G., JUAN CARLOS; LÓPEZ-N., JUAN CARLOS; BUSTILLO-P., ALEX E. (Revista Colombiana de Entomología, 2004)
The effect of two native entomopathogenic nematodes Heterorhabditis sp. (Rhabditida: Heterorhabditidae) and Steinernema sp. (Rhabditida: Steinernematidae) was studied in doses of 125.000, 250.000 and 500.000 infective juveniles (IJ) per tree base on populations of the coffee berry borer, Hypothenemus hampei. During the first coffee harvest of 2001, there were no statistical differences between treatments for the infestation level in the tree due to the high variability of the number of fruits with which the experiment began. For the second coffee harvest of 2001, the percentage of mortality of the coffee berry borer with the two species was 53 and 88%, a month after their application, statistically different (p<0,05) in relation to the control (6%). Five of the six evaluated treatments had average percentages of borer infestation in the tree (PPlA) lower than the control 9,93 ± 1,81 (mean ± S. E), particularly the applications of Steinernema sp. (500.000 IJ/plate) with a PPIA of 4, 17 ± 0,57 and Heterorhabditis sp. (250.000 IJ/plate) with PPIA of 5,62 ± 1,24. This reduction is equivalent to 58 and 43,4%, respectively, in relation to the control. This reduction can be explained by observing the mean percentages of mortality of coffee berry borer life stages in fruits the ground (PMB), which fluctuated between 13,64 and 42,27% for each species of nematodes. Thirty days after application, this difference is well established, with significant differences compared to the control (p<0,05). In conclusion, these nematodes penetrate the fallen fruits 011 the ground, mainly parasitize immature stages and reproduce in lhese insects within the fruit to reduce the populations of coffee berry borer in coffee plantations.